Transformações nas práticas profissionais em publicidade : como qualificar o trabalho neste campo de atuação? - Valente, Tais Bitencourt (2023)
Communication, dealing here specifically with Advertising, needs reflections on a professional field – in an economic and social context – in constant mutation. This study contributes to this end by understanding current working conditions in advertising, considering critical reflections on flexibilization versus precariousness, and the elaboration of principles that guide qualification movements in advertising activity. From conducting in-depth interviews with professionals working in the five regions of Brazil, it was possible to draw an overview of working conditions in the country and, from the perspective of those who experience the activity on a daily basis, aspects that need to be qualified were also identified. in the work activity in question. As the second phase of data collection for this study, two focus group sessions were held, composed of actors who are part of the field of advertising to discuss the aspects to be qualified in the profession, suggesting ways to accelerate changes in advertising practices. And finally, based on the findings obtained in the last phase of the empirical research, principles were elaborated that guide the qualification of work in advertising. From the results of this study and understanding that the practices reproduce dimensions of the social world at the same time that they operate in the formation of this world, it is believed that it is possible, in addition to the conscious formation of new professionals with more capacity to adapt to a area in constant mutation, the promotion of changes in professional practices in this field of activity, with a view to healthier, fairer and more satisfactory work relationships